Representation of Social Stigma Through Expressive Speech Acts in the Novel "Perkumpulan Anak Luar Negeri" by Grace Tioso - Moh Tsalis Fahmi; Sutardi Sutardi; Daniar Sofeny (EDUJAVARE: International Journal of Educational Research, 2026)
This study examines the representation of social stigma through expressive speech in the novel Perkumpulan Anak Luar Nikah by Grace Tioso. Expressive speech used between characters not only serves as an emotional expression, but also as a means of formation, reproduction, and resistance to social stigma. This research aims to describe the form of expressive speech and analyze the representation of social stigma that is manifested through the speech of the characters in the novel. The method used is qualitative descriptive with a contextual pragmatic approach. Data in the form of speech between characters containing expressive speech was collected through reading and recording techniques, then analyzed using Searle's theory of expressive speech, Goffman's concept of social stigma, and the mechanism of stigma according to Link and Phelan. The results of the study showed that there are four forms of expressive speech, namely mocking, criticizing, complaining, and expressing dislike. The four forms represent social stigma through the mechanisms of labeling, stereotyping, separation, status loss, and discrimination against figures based on their birth status, ethnic identity, and social position. In addition to representing the reproduction of stigma, expressive speech also depicts the psychological impact and resistance of characters to social discrimination. This study confirms that pragmatic studies can reveal the social dimension of language in literary works, as well as show the role of language in shaping and opposing stigmatizing practices in society.